Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids

Synthesis and characterization of bifunctional ethenylene bridged mesoporous organoaluminosilicates - Shylesh, S.; Kapoor, Mahendra P.; Juneja, Lekh R.; Srilakshmi, Ch.; Singh, A. P. (Nanoscience and Nanotechnology Letters, 2011)
Bifunctional mesoporous organosilicas having -CH=CH- bridges and aluminium in tetrahedral coordination with tailorable pore sizes have been synthesized using a one-step templating method using cationic surfactants of different chain lengths. Unlike the conventional EtOH-HCl template extraction process, EtOH-NH(4)NO(3) was used as the surfactant-extracting medium and chemical analysis results suggest that through this procedure the mesoporous structure can be retained and dealumination can be minimized. The surfactant-extracted mesoporous solids display high surface area, pore volume and the pore size of the material varies in the range 2.6-3.6 nm, with respect to the alkyl chain length of the cationic surfactant. XRD and nitrogen physisorption studies further proved that the organosilicas are hydro thermally stable than the conventional Al-MCM-41 materials and their better stability is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethenylene groups in the wall positions. The coupling of Al(4) with -CH=CH- bridges offer new prospects for the application of periodic mesoporous organosilicas in heterogeneous catalysis.
Keywords: Aluminium; Cationic Surfactants; Hydrothermal stability; Organosilicas